Using field notes to facilitate critical reflection. Issue 2 (3rd March 2016) - Maharaj, Nandini
Abstract: Taking field notes is an integral part of documentation and analysis in qualitative research. In this paper, the author describes how field notes can be used to facilitate critical reflection when engaging in fieldwork. Examples are used to sensitize novice researchers to the following considerations: (1) researchers' status as an insider or outsider; (2) their location on the continuum of observer to participant; and (3) subjectivity in the research process. Through critical reflection, researchers are better prepared to produce descriptions that provide the foundation for analytical writing and conceptual reasoning. The paper aims to make this process more transparent.